Psychometric validation of the Environmental Reward Observation Scale (EROS) in breast cancer survivors - Fernández-Rodríguez, Concepcion; González-Fernández, Sonia; Pedrosa, Ignacio (Anales de Psicología / Annals of Psychology, 2020)
The loss of rewards resulting from oncological disease has been associated with emotional problems in cancer survivors. The Environmental Reward Observation Scale (EROS) evaluates environmental reinforcement and is based on behavioral models which show the relationship between environmental reinforcement and emotional state. The aim of this study is to analyze the psychometrical properties of this scale in breast cancer survivors and its usefulness in discriminating between survivors with and without emotional disorders. A total of 219 women survivors (Mage= 52.97; SDag= 7.50) completed measures of environmental reinforcement, behavioral activation and avoidance, and emotional state. Data fit an essentially unidimensional structure, showing high internal consistency and correlations, varying from moderate to high, with all the measures used. In the EROS scores, statistically significant differences were found between participants with and without emotional disorders. Optimum cut-off point to discriminate between anxiety and depression was established via Receiver Operating Characteristic curve. Using the framework of the Item Response Theory model, all the items were found to have a power of discrimination for measuring environmental reinforcement ranging from moderate to high. The EROS is a psychometrically sound instrument, which can be used to improve assessment of emotional state in breast cancer survivors.